PENGARUH MEDIA VISUAL PROYEKSI POWER POINT DAN MINAT TERHADAP HASIL BELAJAR PESERTA DIDIK - Siska Febriyanti S (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
This study aims to reveal: (1) the effect of visual media projection with Power Point on Economics learning outcomes, (2) the effect of students’ learning interest on their Economics learning outcomes, (3) the interaction between media used and learning interest students’ Economics learning outcomes in MAN 2 Batusangkar. The type of research is Quasy Experiment using factorial 2x2 design. The population was grade X students at MAN 2 Batusangkar. The sampling technique was cluster sampling; class X-2 as the experimental class and class X-5 as the control class. Data analysis techniques are descriptive analysis and inductive analysis using two-way ANOVA. The results of the study show: (1) the students taught using Visual Media Projection with Power Point have higher learning outcomes compared to those taught with Non-Projection Visual Media with Chart, (2) the students having high interest in learning gained higher Economics learning outcomes than those with low interest in learning, and (3) There is no interaction between the use of instructional media and learning interest in students’ learning outcomes in Economics. Finally, it is recommended that teachers should use computer-based learning media, such as visual media projecting Power Point effectively as an alternative to improve students’ learning outcomes.